PERBANDINGAN HASIL BELAJAR MENGGAMBAR BUSANA ANTARA MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE DAN MODEL PEMBELAJARAN KONVENSIONAL PADA SISWA SMK NEGERI 8 MEDAN - Halida Hanim; Fitria Fazilah (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACT This study is aimed at determining the differences in student learning outcomes using example and non example learning model with conventional learning models in fashion drawing subjects in class XI course fashion.The samples were two randomly selected classes, each class consisting of 30 students. The first class in example non example the teaching and learning model and others in the class teaching using conventional learning models. Instrument of data collection is observation sheet. Data were analyzed using t-test analysis technique.Based on the calculations, the price of 0,98 t> t 2.00 at the 5% significance level, the hypothesis which states that there is a significant difference in learning outcomes between the results of learning to draw clothing using learning model example and non example with conventional learning model on students XI classes dressmaking courses is accepted. Kata Kunci : Menggambar busana, model pembelajaran example non example.